A Two-Step Optical Modified Signed-Digit Adder for Large-Scale 2D Data Array Using Digit-Decomposition-Plane Representation - Alsheraidah, Sabah S.; Alebadi, Mohammed A.; AI-Saffa, Alaa A. (Basrah Journal for Engineering Sciences, 2010)
In this paper, parallel optical array adder fur large-scale 2D Modified Sign-Digjt (MSD) data array is proposed. and implemented to limit the cany propagation to constant steps. The digit-decomposition-plane (DDP) representation technique is expanded to code the 2D an-ay of the MSD nwnber system. The design is based on the logical fonnul.as which are newly derived according to the fundamental parallel addition algorithm for MSD number system using the . . . . featur of the DDP coding technique. The optical im plementations scheme is based on classical optical elementS sucb NJ spatial light modulators, ooam combiner.;, beam splitters, mirrors, light source anays, and light detector arrays. The proposed algorithm and itS optical architecture ve useful intrinsic characteristics such as ultra-high speed, constant processini time, and parallel computation on large-scale data arrays. The simulation results insure lhat the proposed arithmetic unit is worked successfully.